2011
DOI: 10.1017/s0014479711000482
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Cereal, Vegetable and Grape Production Systems in Urban and Peri-Urban Agriculture of Kabul, Afghanistan

Abstract: Little is known about the economics of urban and peri-urban agriculture in Kabul, Afghanistan. This study therefore aimed to investigate the profitability of 15 mixed cropping farms with a total of 42 farm plots that were selected from a survey of 100 households (HHs). The sample represented the three dominant farm types: cereal producers (15 plots), vegetable farmers (15 plots) and grape producers (12 plots). A cost-revenue analysis of all inputs and outputs (costs of tillage, seed where applicable, weeding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Given these exclusions, we would estimate that the areas of urban croplands found in this analysis are fairly conservative and underestimate the actual area of urban and peri-urban crop production. Additional case studies of urban agriculture focusing on urban and peri-urban plots found higher proportions of vegetable production [33][34][35] than were found in the types of urban croplands captured in our analysis suggesting that this analysis may also be underestimating the extent of vegetable and fruit production in urban croplands.…”
Section: Limitationsmentioning
confidence: 58%
“…Given these exclusions, we would estimate that the areas of urban croplands found in this analysis are fairly conservative and underestimate the actual area of urban and peri-urban crop production. Additional case studies of urban agriculture focusing on urban and peri-urban plots found higher proportions of vegetable production [33][34][35] than were found in the types of urban croplands captured in our analysis suggesting that this analysis may also be underestimating the extent of vegetable and fruit production in urban croplands.…”
Section: Limitationsmentioning
confidence: 58%
“…During farmers' crop and fruit harvests, samples of about 300 g fresh weight of all extracted (marketed and dedicated to autoconsumption) plant parts and residues of vegetables, cereals, and grapes were taken from five points in the field, pooled, weighed, dried to constant weight at 60°C for 48 h, and weighed again for moisture-content correction. Subsamples of dried yield components (Safi et al, 2011) were ground with a mill (T-Tecator Cyclotec 1093, Höganäs, Sweden) to a size of 0.5 mm, and stored in sealed polyethylene bags until analysis of N, P, K, and organic C.…”
Section: Measurements Of Nutrient Inputs Outputs and Leaching Lossesmentioning
confidence: 99%
“…What percentage of the existing urban area needs to be devoted to UA to meet the vegetable consumption of urban dwellers in different countries of the world? Although a significant number of people, especially in developing countries, produce staple crops through UA (Maxwell 1995, Safi et al 2011, Zezza and Tasciotti 2010, we restricted our study to vegetables for several reasons. First, comparing global annual harvested areas for vegetables and cereals to global urban area highlights the limited potential contribution of UA to global cereals production (table 1).…”
Section: Introductionmentioning
confidence: 99%
“…First, comparing global annual harvested areas for vegetables and cereals to global urban area highlights the limited potential contribution of UA to global cereals production (table 1). Second, studies suggest that, compared to staple crops, the production of high-yielding, high-value and perishable products like vegetables often represent the most profitable UA endeavor and constitute a substantial fraction of UA production in practice (Lee-Smith 2010, Safi et al 2011, Vagneron 2007). Finally, a key contribution of UA is in increasing the dietary diversity through the incorporation of vegetables into the diet to address food insecurity (Frison et al 2006, Welch and Graham 1999, Zezza and Tasciotti 2010.…”
Section: Introductionmentioning
confidence: 99%